Microbial synthesis of titanium dioxide nanoparticles and their importance in wastewater treatment and antimicrobial activities: a review - Rathore, Chandani; Yadav, Virendra Kumar; Gacem, Amel; AbdelRahim, Siham K.; Verma, Rakesh Kumar; Chundawat, Rajendra Singh; Gnanamoorthy, G.; Yadav, Krishna Kumar; Choudhary, Nisha; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Microbiology, 2023)
Nanotechnology (NT) and nanoparticles (NPs) have left a huge impact on each and every field of science today, but it has shown tremendous importance in the field of cosmetics and environmental cleanup. NPs with photocatalytic effects have shown positive responses in wastewater treatment, cosmetics, and the biomedical field. The chemically synthesized TiO2 nanoparticles (TiO2 NPs) utilize hazardous chemicals in order to obtain the desired shaped TiO2. So, microbial-based synthesis of TiO2 NPs has obtained popularity due to its eco-friendly nature, biocompatible, etc. Being NPs, TiO2 NPs have a high surface area-to-volume ratio in addition to the photocatalytic degradation nature. In the present review, authors have emphasized the microbial: algae, bacterial, fungi, and virus-mediated synthesis of TiO2 NPs.